GREEN ECONOMY AS A KEY ASPECT OF NATIONAL DEVELOPMENT (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The green economy represents an innovative development model aimed at achieving sustainable economic growth while simultaneously reducing environmental impact and promoting more rational use of natural resources. In the context of global climate change, shrinking biodiversity, and ecosystem degradation, the transition to a green economy becomes an urgent task for all nations, especially for developing countries. This article explores the role of the green economy as a key factor in socio-economic and environmental progress. It analyzes the core principles, implementation mechanisms, and the potential for national-level adaptation. Special attention is given to international experiences in implementing green strategies and their applicability to Uzbekistan. The article also examines existing challenges, barriers, and prospects for transitioning to a green model, as well as the roles of government, business, and society in ensuring a sustainable future.